Hubungan Antara Kadar Hemoglobin, Jumlah Eritrosit dan Jumlah Eosinofil Terhadap Lama Kerja pada Penambang Pasir di Gemampir, Klaten - Endang Widhiyastuti; Meilya Tiksna Wahyu Baswara; Niken Kusuma Dewi; Olivia Ratasha Apriani (Journal of Innovative and Creativity, 2025)
Sand miners are workers engaged in extracting sand from land, rivers, coastal areas, or the sea for construction purposes. This occupation poses health risks due to exposure to dust, silica, and microorganisms, which may trigger oxidative stress, chronic inflammation, and alterations in hematological parameters. This study aimed to analyze the relationship between hemoglobin levels, erythrocyte counts, and eosinophil counts with the working time among sand miners in Gemampir Village, Klaten. This was an analytic study with a cross-sectional design. A total of 32 male respondents were selected using purposive sampling from a population of 60 miners. Data were collected through questionnaires and venous blood examination analyzed with a Sysmex XN-330 Hematology Analyzer. Pearson’s correlation test was applied for hemoglobin and erythrocytes, while Spearman’s correlation was used for eosinophils, with a significance level of p < 0.05 and p < 0.01. The results showed that most respondents had hemoglobin (88%) and erythrocytes (72%) within the normal range, while eosinophils varied, with 44% above normal. Correlation analysis revealed working time was not significantly associated with hemoglobin (p = 0.082) or erythrocytes (p = 0.260). In contrast, a significant relationship was found between working time and eosinophil counts (p < 0.001), indicating chronic inflammatory responses due to dust exposure. In conclusion, working time among sand miners was more strongly associated with increased eosinophils than with changes in hemoglobin or erythrocytes. Eosinophil count can serve as a sensitive biological indicator of dust exposure effects, highlighting the importance of personal protective equipment, healthy lifestyle practices, and regular health monitoring for miners.